Nursing students' perceived stress, coping strategies, health and supervisory approaches in clinical practice: A Slovak and Czech perspective - Gurková, Elena; Zeleníková, Renáta (Nurse education today, 2018)
To investigate the relationship between supervisory approaches in clinical practice on the one hand, and nursing students' level of experience, perceived stress, coping strategies and physio-psychosocial status on the other. A cross-sectional descriptive study. The sample consisted of 275 nursing students enrolled in bachelor's degree programs in the Czech Republic and Slovakia. Participants provided data on background characteristics as well as completing the following instruments: Perceived Stress Scale; Physio-Psycho-Social Response Scale, and Coping Behavior Inventory. Relationships were examined by parametric Pearson correlations and multiple regression analyses. For group comparisons, multi-factor analysis of variance procedure was performed. Experienced nursing students perceived higher levels of stress than novice students. Slovak students subject to traditional group supervision by nursing teachers reported higher stress levels related to teachers, peers, lack of professional knowledge and skills, while also reporting a higher frequency of avoidance behaviors; and less frequent problem-solving activity than Czech students under individual supervision by clinical mentors. Clinical stressors accounted for 22% of variance in the students' physical, psychological and social health. Academic stressors accounted for only 5% of variance and avoidance behaviors only 2% of variance in student's physical, psychological and social health. These results suggest that the stress or anxiety perceived by nursing students is acounted for mainly by clinical stressors. Further studies should focus on identifying other predictors (personal, external) of students' physical, psychological and social health and also examine the effectiveness of specific stress management programs and, individual supervisory approaches in reducing the intensity and, the negative effects of stressors. •Stress perceived by nursing students is acounted for mainly by clinical stressors.•Students' physical, psychological and social health is strongly influenced by clinical stressors.•Experienced students perceived higher levels of stress than novice students.•Methods of clinical supervision had a significant impact on different domains of stressful events.